Desenvolvimento de material didático digital de língua inglesa na perspectiva de sala de aula invertida - Pletsch, Edoardo (2018)
The Internet has been a channel for easy access to information. In it we find an infinity of content: educational, professional, recreational, etc. With the advent of Web 2.0 (O'Reilly, T, 2004), technology has been an ally in learning in the various educational spheres. In contrast, the traditional learning model with expository and teacher-centered classes is still in place. Therefore, a reformulation of the traditional model to the lecture room, decentralizing the teacher's attention and bringing the student to the center of the educational process, is that the inverted classroom is proposed (JONATHAN; BERGMANN, 2016; VALENTE, 2011; BOTTENTUIT JUNIOR et al BACICH et al., 2015). At the Center for Research, Teaching and Learning of Distance Languages (NUPEAD), we identified the need to fill a gap regarding the practice of oral production in courses already offered in the laboratory. Therefore, in this study, conducted in the Professional Program in Educational Technology Network (PPGTER), with the line of Educational Technology Development Research Network, we propose to develop a digital pilot course of English language in the hybrid mode in view of the inverted classroom, pre-intermediate level, which was named as ResPOnD - Read and Speak Online Dinamically. Adopted for the current language teaching view as a social practice (ROTH, 2006, 2008, ROSE; MARTIN, 2012) which provides stage as the language of instruction by allowing students to carry out activities in MDD that purport to deconstruction and collaborative construction of genres for a later individualized construction, aiming to effect the learning in the target language solving problems and to practice the language reconstructing the proposed gender, having the teacher as mediator of this practice. For this, a case study was carried out in order to ascertain the necessary data for the elaboration of digital didactic material through a questionnaire applied to the academic community of UFSM. The data from the pilot application were analyzed qualitatively through the application of a diagnostic and evaluative questionnaire to the final participants of the course. The results indicate that the course in the format of the inverted classroom was satisfactory, although in its pilot version, there is a need for adaptations to work, mainly orality in an integrated way to other skills. In addition, this experience showed positive results regarding the proposed on-site activities, as they helped students to practice English when inserted into collaborative activities. The proposed MDD was adequate and according to the course proposal because the Before Class, During Class and After Class moments were added to the teaching of language adopted in the course. The tools linked to the course such as Online Voice Recorder, WeVideo, Google Drive as well as the activities proposed for the development of orality in an integrated way were catalysts of the teaching and learning processes showing satisfactory production in English language.